Development of a Broadband Telemedical Network Based on Internet Protocol in the Asia-Pacific Region - Nakashima, N.; Shimizu, S.; Okamura, K.; Hahm, J. S.; Kim, Y. W.; Han, H. S.; Torata, N.; Antoku, Y.; Lee, Y. S.; Tanaka, M. (Methods of Information in Medicine, 2007)
Objectives: To promote the exchange of knowledge and standardization of medical procedures and medical systems in the Asia-Pacific region, we established a medical networkwith high-quality moving images over broadband Internet lines in February 2003.Methods: Real-time teleconferences and live demonstrations with medical-qualityvideos, broadcastvia the Digital Video Transport System, have been used t teach surgical techniques and other medical procedures across national borders.The Asia-Pacific Advanced Network (APAN) committee in August 2005 formally approved our proposal to establish a medical working group within APAN. The networkwas expanded by the launch of the Trans- Eurasia Information Network 2 in 2006. By the end of 2006, we had conducted 82 events, in 10 countries in the Asia-Pacific region. The multi-station event has increased everyyear.Results: There have been no serious transmission problems or ethical conflicts so far. With these experiences and current achievements, we hope to extend this advanced network system to the entire Asia-Pacific.Conclusion: This system is a promising and very useful tool for the standardization of medical system and procedures across national borders. Drawing upon these experiences and current achievements, we hope to extend this advanced network system to the entire Asia- Pacific region.
Keywords: Telemedicine; international educational exchange; medical informatics